Nonlinear properties of circular solid-core photonic crystal fiber with air-hole diameter difference and spacing in the cladding - Le, Tran Bao Tran; Dang, Van Trong; Chu, Van Lanh; Nguyen, Thi Ha Trang; Hoang, Trong Duc; Nguyen, Thi Thuy (Hue University Journal of Science: Natural Science, 2022)
We emphasize the ability to control the nonlinear properties of silica-based circular solid-core photonic crystal fibers (PCFs) with a new design. In this fiber, the diameter of the air hole in the rings is different, and the lattice constant is ununiform in the cladding. The simulation results show that a near-zero ultra-flattened chromatic dispersion over a wide wavelength range and low attenuation in these PCFs is achieved. Two structures with the lattice constant, Ʌ, of 0.7 and 0.9 µm and filling factor, d1/Ʌ, of 0.45 in the first ring were selected and investigated in detail. These structures are capable of generating broad-spectrum supercontinuum.